2010
DOI: 10.1007/s10763-010-9234-3
|View full text |Cite
|
Sign up to set email alerts
|

Are Students Prepared to Communicate? A Case Study of an Australian Degree Course in Biotechnology

Abstract: Public concerns about biotechnology have resulted in greater attention being paid to the mechanisms by which biotechnology is communicated with non-scientists, including the provision of science communication training. As undergraduate and postgraduate courses form the foundation of the biotechnology sector by providing a pipeline of university graduates entering into the profession, it has been proposed that formal science communication training be introduced at this early stage of career development. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…Similarly, a review of science funding policies from around the world found that many funders wanted researchers to disseminate the results of their work beyond academia, but very few mentioned a need for investigators to meaningfully engage with members of the public (Palmer & Schibeci, 2014). One study found that biotechnology students did not feel prepared to communicate with the public about their work and were unfamiliar with the idea of dialogue‐based science communication (Edmondston, Dawson, & Schibeci, ). The same researchers also found that instructors thought that getting better and more dialogue‐focused communication training into the curriculum would be difficult (Edmondston & Dawson, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, a review of science funding policies from around the world found that many funders wanted researchers to disseminate the results of their work beyond academia, but very few mentioned a need for investigators to meaningfully engage with members of the public (Palmer & Schibeci, 2014). One study found that biotechnology students did not feel prepared to communicate with the public about their work and were unfamiliar with the idea of dialogue‐based science communication (Edmondston, Dawson, & Schibeci, ). The same researchers also found that instructors thought that getting better and more dialogue‐focused communication training into the curriculum would be difficult (Edmondston & Dawson, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is value in developing literacy skills early in an undergraduate curriculum to provide a good foundation for the students (Freeman & Lynd-Balta, 2010). Furthermore, as a significant portion of undergraduate students will not undertake studies at a postgraduate level, inclusion of science communication training in undergraduate courses becomes even more significant (Edmondston, Dawson & Schibeci, 2010a). It is also proposed that formal science communication training should be introduced in early stages of career development as this form of training will place the students in a better stage as they begin their careers as willing and able scientists after they graduate (Edmondston, Dawson & Schibeci, 2010b).…”
Section: Teaching Oral Communication and Presentation Skills In Undermentioning
confidence: 99%
“…Therefore, it is a process to be thoughtfully prepared and a positive feedback from our interviewees is encouraging. However, several research warn that in spite of being aware of the issue importance, graduate students severely lack the skills of speech clarity (Haworth and Garrill, 2003;Longnecker, 2009;Edmondston et al, 2010). Another related concept is conciseness so we asked the interviewees to rate the importance of delivering concise speech.…”
Section: Speaking Skillsmentioning
confidence: 99%